2D MXene: MXene‐Based Nonlinear Optical Information Converter for All‐Optical Modulator and Switcher (Laser Photonics Rev. 12(12)/2018). Issue 12 (13th December 2018) - Wu, Leiming; Jiang, Xiantao; Zhao, Jinlai; Liang, Weiyuan; Li, Zhongjun; Huang, Weichun; Lin, Zhitao; Wang, Yunzheng; Zhang, Feng; Lu, Shunbin; Xiang, Yuanjiang; Xu, Shixiang; et al.
Abstract : In article number1800215, Shunbin Lu, Shixiang Xu, Han Zhang, and co‐workers demonstrate that two‐dimensional MXene exhibits strong nonlinear optical response at the visible‐light region due to the optical Kerr effect. When the laser beam passes through the MXene, the diffraction rings can be excited with spatial self‐phase modulation techniques. Moreover, the MXene is developed as the information converter to realize the modulation of pump light to probe light in an all‐optical switcher/modulator.